Identification of Learning Resource Access in Improving Student's Knowledge in Linguistic Rules at MIN 3 Tapin - Hafizah, Elma Nur; Muna, Khairiatul (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
This research is to identify access to learning resources in increasing students' knowledge into linguistic rules at MIN 3 Tapin. By using mixed method concurrent triangulation on 40 students at MIN 3 Tapin, the Miles and Huberman analysis technique was applied to qualitative data and for quantitative data the classical assumption test, simple linear regression test and hypothesis testing using SPSS 16.0. The results stated that students have various access to learning resources as seen from the results of questionnaire answers regarding access to learning resources, then supported by the results of interviews and documentation which states that the facilities at MIN 3 Tapin are adequate, making it easier for students to access learning resources at MIN 3 Tapin. Students' knowledge into linguistic rules seen from the results of test questions and interviews shows that they are still at a sufficient level and need to be given further evaluation. Access to learning resources that is considered quite adequate apparently does not have a significant influence on knowledge of linguistic rules, students who have access to various sources of access to learning resources are not guaranteed to have good knowledge into linguistic rules.